Aproximación a la masonería española en Estados Unidos - Cuartero Escobés, Susana (2015)
This article analyses the opening of Spanish Masonic lodges in the United States. It is quite surprising that between approximately 1890 and 1920, the U.S. had more than forty Spanish lodges in a territory where American Freemasonry already existed. Why is this fact given? Who was behind the Spanish lodges? What were their concerns? These are questions that this work will try to answer, keeping in mind that documents are from different lodges, and in most cases scarce and highly fragmented.